Project Report on Micro-Computer Based Industrial Process Controller - MATHUR V S and SRINIVAS (1990)
INTERNAL GUIDE:ANANTHARAM, MVJCE EXTERNAL GUIDE:LELE M V, OFFICER
Keywords: Micro-Computer Based Industrial Process Controller